Water quality assessment of Jarum Mas River at Matang Mangrove Forest, Perak - Gandaseca, Seca; Tindit, Albert Empawi; Mohamad Pazi, Ahmad Mustapha; Nyangon, Laurna (Alkhaer Publications, 2018)
Mangrove Forest is well known with the mangrove tree that can withstand waves from the sea and even Tsunami. That has happened in Sri Lanka in 2004 where many villages at the mangrove area safe and the number of death reduced. However, this mangrove forest nowadays threatened by the human activities. Therefore, the study was carried out to determine the water quality index (WQI) of Jarum Mas river which near to the agriculture area and to compare the water quality during low and high tide. There were 30 samples of water taken during Jun and July at 5 stations along Jarum Mas river. The data collections were collected based on the six WQI parameters; Ammoniacal nitrogen (NH3-N), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), pH, Total Suspended Solids (TSS) with other five parameters; Electrical Conductivity (EC), Turbidity, Total Dissolved Solids (TDS), Salinity and Temperature. The results for each parameter are summarized as follow; NH3-N range (4.3-4.85 mg/l), BOD range (1.5-4.2 mg/l), COD range (1095-1405 mg/l), DO range (2.27-4.91 mg/l), pH range (6.86-6.98), TSS range (48.33-70.5mg/l), EC range (33.04-38.7 mS/cm), turbidity range (19.38-26 NTU), TDS range (20.07-22.69 mg/l), salinity range (19.5-22.03 PSU), temperature range (28.25-29.35 oC). The WQI of Jarum Mas River is Class III which need extensive treatment for water supply and only common economic value for fishery based on Water Quality Index (WQI) and Interim National Water Quality Standards for Malaysia (INWQS) by Department of Environmental Malaysia.